ANALYSIS OF DIAGRID STRUCTURE SYSTEM WITH STIFFNESS BASED METHOD AND ITS COMPARISON WITH CONVENTIONAL STRUCTURAL SYSTEM - Angga Prawira, Pradana
High rise buildings continue to develop from time to time to meet human needs, limited resouces and expensive land especially in urban areas. But in modern era the needs of high rise building not only centered on structural efficiency but also versatile appearance and aesthtetic feature, one of the answer to building needs that meets with the time is diagrid structural system. Diagrid is another form of structural system, diagrid formed from diagonal shaped frames that connected each other, diagrid material can consist of steel, concrete or lumber. The term diagrid is combination of words “diagonal” and “grid” which refers to structural system that gets structural integrity through the use of triangulation or triangle formation. The diagrid structure system often uses diamond shapes to increase stifness Diagrid is not a new structural system, one of the earliest building that use diagrid structural system built in 1960, but expensive cost and limited technology makes diagrid development stagnated, at the early 2000 building that use diagrid structural system start to appear again. In diagrid there is two main term, that is module and node. Module is number of crystaline configuration floors, start from at the end of diagomal member at the bottom floor module to end of diagonal member at the upper floor module. Node is the point of intersection of the diagonal member, one diagrid module can consist of 2 to 10 floor or more. The selection of module and node diagrid will affect structural efficiency, appearance and cost of diagrid building, so that the module and node design must be carried out very accurately and very carefully. Stiffness based method is the equation that was first proposed by Kyoung Sun Moon in 2007. This method is used to obtain the diagonal member cross section dimensions of the diagrid structural system. The equation procedure starts by determining the total contribution of displacement of stcruture due to bending and shear deformation. This designation is based of the assesment of diagrid intrinsic atributtes and behaviour of high rise building characteristic that are related to the ratio between the height versus width of the building and leads to deformation values required by shear and bending. Furthermore the simpe equation proposed by Moon changes the deformation values needed to cross sectional area for the diagonal member diagrid structure. The purpose of this study is to determine the performance of diagrid building structure when compared to conventional building and how the optimal diagonal member configuration for the diagrid building. There are 4 types of building models to be reviewed, consists of 1 conventional building model and 3 diagrid building models with different diagonal member configurations. The building models will be analyzed using program ETABS and follow the applicable provisions in Indonesia. The building models is assumed to be located in the DKI Jakarta with soft soil sites classification. The result of the analysis that will be compared include cross sectional dimensions at the building periphery, total weight and base shear of the building, performance of service limits, time period and the ratio between capacity and load of structrure components at the building periphery. From the observations made between the diagrid building and conventional building it is known that diagrid building has a better structural performance. The stiffness based equation method that used to obtain diagonal member cross sections dimensions of the diagrid buidling also very helpful to reduce the iterative process, but the diagonal member cross sections dimensions obtained from this method have a quite big ratio between capacity and load so the cross section dimensions seems wasteful and excessive. However the stiffness based method can be used as an initial reference to determine the diagonal member cross section of diagrid building